2020
DOI: 10.3389/fchem.2020.00479
|View full text |Cite
|
Sign up to set email alerts
|

Single and Mixed Feedstocks Biorefining: Comparison of Primary Metabolites Recovery and Lignin Recombination During an Alkaline Process

Abstract: Cannabis sp. and Euphorbia sp. are potential candidates as indoor culture for the extraction of their high value-added metabolites for pharmaceutical applications. Both residual lignocellulosic materials recovered after extraction are studied in the present article as single or mixed feedstocks for a closed-loop bioprocesses cascade. An alkaline process (NaOH 3%, 30 min 160 • C) is performed to separate the studied biomasses into their main components: lignin and cellulose. Results highlight the advantages of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…To overcome this drawback, some samples of BSGs from different origins could be pooled and processed at a single high-capacity industrial site. However, our previous work has shown that this pooling was not strategic, but rather the opposite, especially for samples with fluctuating protein levels, which is the case in this study (Berchem et al, 2020).…”
Section: Resultsmentioning
confidence: 59%
See 3 more Smart Citations
“…To overcome this drawback, some samples of BSGs from different origins could be pooled and processed at a single high-capacity industrial site. However, our previous work has shown that this pooling was not strategic, but rather the opposite, especially for samples with fluctuating protein levels, which is the case in this study (Berchem et al, 2020).…”
Section: Resultsmentioning
confidence: 59%
“…Cellulose and hemicellulose contents were obtained on the basis of the quantification of the constituent monosaccharides, namely, glucose for cellulose, and the sum of arabinose, xylose, rhamnose, mannose and galactose for hemicellulose according to an adapted published protocol (Berchem et al, 2020). First, 100 µL of an internal standard solution (2-deoxy- d -glucose, 3 g L −1 ) was added to 900 µL of the Klason hydrolysate.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It generates alkali lignin (AL) under various temperatures with pH values generally higher than 10. Furthermore, there are numerous hydroxyl groups on the surface of AL, and etherified phenolic acid groups exist, which play an essential role in cross-linking. In the current pulping industry, alkaline pretreatment is mainly used for the delignification of nonwood feedstocks, such as bagasse, wheat straw, and hemp …”
Section: Lignin As Byproducts From Biorefineriesmentioning
confidence: 99%